The effects of climate change on household food production in rural Makhado Local Municipality, Limpopo Province - Madzivhandila, Thanyani Selby (University of Limpopo, 2015)
The thesis of this study is that food production systems for self-provisioning have historically constituted the backbone for survival and life-support in rural South Africa. Colonialism and apartheid capitalism bore harsh effects on the food production life support systems. However, these effects pale into insignificance compared to the present devastation of the food production systems associated with climate change. The contribution of rural South Africa towards climate change is at all scale negligible because poor people hold limited capacity to produce the deleterious gas emissions that allegedly causes global warming. However, the poor are disproportionately exposed to the adversarial effects of climate change and their food production systems have demonstrated beyond doubt that they cannot cope with stressors occasioned by climate change. Government policy and measures continue to be inadequate and inaccessible for rural households that produce for self-provisioning. The thesis further demonstrate that scientifically–based intervention measures adopted among rural poor in developing countries are viewed as alien and therefore not wholeheartedly adhered to by the users. The thesis points to this discrepancy to illustrate that the value systems among the rural population in South Africa describe changes in their food production in terms of climatic conditions that are, according to their belief systems, avoidable consequences of people’s conduct of life outside tradition, religion and so on. It engages a nascent argument relating to the failure of private and public scientifically-generated intervention measures within developing countries’ rurality, which is ironically exacerbated by the apparent inappropriateness and, often, destructiveness vi of the Green Revolution Technologies. As such interventions fail, the thesis points, they create skeletons of evidence, that appear to corroborate the traditionalist belief systems about the locus of causes of change in climatic conditions being extra-terrestrial as a consequence of people’s misconduct of life. The study investigates the effects of climate change on household food production systems in rural Makhado Local Municipality. 30 villages are used for this study in both households questionnaire survey, interview of the key informants and observation of different patterns of production process, geo-spatial features and current settlements patterns. The data analysis results reflect that different households within the municipality experiences variety of effects of climate change. Furthermore, the climatic conditions which consisted of enough reliable precipitation during food production stages have declined; rather in the post-1990 period, the area have been experiencing continuous heatwaves and drought which destroyed household’s crops and livestock. Using the normative and historical research designs the study found that the situation within villages has changed drastically because of climate change when comparing the conditions preand post-1990. The deliberate adoption of the historical design was crucial given that the thesis mission was to highlight the discrepancies in the so-called modern systems versus the traditionalist philosophies that continue to dominate the thinking and action rural populations in most developing countries. Equally, the historical design provides unquestionable possibility of applying appropriate research techniques to contextualize the research problem under investigation. Indeed, this manoeuvre has always been an important part and parcel of the research design and methodology because the thesis vii had to adopt a longitudinal research orientation through an appropriately designed data collection tool, specifically the questionnaire and interview schedule. From a philosophical perspective, the thesis demystifies the thinking that the so-called scientifically-generated interventions against climate change could resolve the attendant challenges, inclusive of food production. That is, it insinuates that appropriate research is needed for developing countries rurality in order to find intervention measures that are a product of the evolution of traditionalist value systems. Tacitly, the thesis challenges the statist and private sector habits of always parachuting the so-called scientifically generated solutions to climate change.
Thesis (Ph.D. (Administration)) -- University of Limpopo, 2015
Keywords: Climate change; Food production; Household; Climatic change -- South Africa; Food industry and trade -- Production control; South Africa -- Climate; Rural poor -- South Africa -- Economic conditions